Effect of preservatives and acidifying agents on the shelf life of packed cracked green table olives from Maçanilha cultivar. (September 2015) - Alves, Maria; Esteves, Eduardo; Quintas, Célia
Highlights: Acidifying agents and preservatives were used to extend shelf life of table olives. Benzoic and sorbic acids resulted in olives with flavour and colour impaired. A mixture of citric and lactic acids resulted in an acceptable strategy to pack cracked olives. Abstract: Cracked green table olives of the Maçanilha cultivar are the most popular fermented food produced and consumed in Southern Portugal. They are processed according to empirical/traditional procedures and are characterized by a natural green colour, a rich aroma and a typical bitter taste. In the present conditions of processing, the olives after packing are not stable having a rather short shelf life mainly due to the leakage of brines and swelling of the containers which contributes to enormous economic losses. The aim of this work was to increase the shelf life of packed olives, studying the effect of acidifying agents (lactic, citric and hydrochloric acids) and preservatives (benzoic and sorbic acids) on the microbiological aspects, physicochemical parameters (pH, acidity, reducing sugars and colour) and overall eating/tasting quality of olives after 158 days. The additives tested prevented the growing of yeasts and Enterobacteriaceae and production of gas during the storage resulting in an increase in the shelf life of olives. The lowest sensory evaluation was attributed to olives preserved with benzoic, sorbic and lactic acids and the highest sensory scores were obtained by olives packed in brines containing the mixture of citric and lactic acid and acidified with hydrochloric acid. The acidification of the brines with the mixture of citric and lactic acids resulted in an acceptable strategy to pack cracked olives. The results obtained could help local industries introduce changes in the existing methods of packing of this Mediterranean food to increase shelf life and prevent economic losses.